SCREENING OF HEPATITIS B AND C AMONG PEOPLE VISITING GENERAL PRACTICE CLINICS IN A RURAL DISTRICT OF SINDH, PAKISTAN - Kumar, Ameet; Lalani, Saima; Afridi, Asad Ali Khan; Khuwaja, Ali Khan (Journal of Ayub Medical College Abbottabad, 2010)
Background: Hepatitis B (HB), Hepatitis C (HC) and their risk factors are amongst the major health problems in developing countries including Pakistan. This study aimed to screen for HB and HC among people who visited General Practice clinics and also to identify the differences of screening positive cases by age and sex. Methods: This was a retrospective study conducted in Tando Muhammad Khan city, one of the rural districts of Sindh. All together we reviewed 5989 laboratory reports of people for hepatitis B and C on consecutive basis from two laboratories. A pre-designed and structured perform was used to collect the required information. Chi-squared test and univariate analysis was calculated to assess the difference in HB and HC proportion by age groups and sex. Results: One-fourth of reports were positive for at least one entity whereas 8% and 17% of reviewed reports of adults (>18 years and above) were screened positive for HB and HC respectively. Positive screened tests were higher among older age group compared to young age group (HB: older age group=56.6% vs. younger age group=43.4%; OR=1.07) and (HC: older age group=58.3% vs. younger age group=41.7%; OR=1.08). In the same way, positive screened tests were higher among men compared to women (HB: men=67.0% vs. women=33.0%; OR=1.2) and (HC: men=62.0% vs. women=38.0%; OR=1.3). Conclusion: A large proportion of people were screened positive for HB and HC in this study. Prevention and screening are suggested at larger scale for urgent planning and implementation of intervention strategies in this regard. Further research is also recommended to explore this important health issue at large scale. Keywords: Screening, Hepatitis B, Hepatitis C, General Practice